Response to 1-Year Fixed-Regimen Bevacizumab Therapy in Treatment-Naïve DME Patients: Assessment by OCT Angiography - Magdalena Hunt; Sławomir Teper; Adam Wylęgała; Edward Wylęgała (Journal of Diabetes Research)
Purpose. To evaluate the effectiveness of intravitreal bevacizumab treatment in patients with diabetic macular edema (DME) by assessing retinal changes using optical coherence tomography angiography (OCT-A). Methods. This prospective study was performed in patients with treatment-naïve DME. The eyes of patients were imaged using a swept-source OCT system with a scan area of 6×6 mm. The DME patients with a central macular thickness (CMT) of ≥300 μm received nine bevacizumab injections within 12 months. The demographic, systemic, and ocular parameters, including the best-corrected visual acuity (BCVA), CMT, microaneurysm (MA) count, and foveal avascular zone (FAZ) area in both superficial capillary plexus (SCP) and deep capillary plexus (DCP), as well as vessel density in SCP, were assessed in the patients. In addition, the response (good or poor) of the DME eyes to bevacizumab treatment and the final visual acuity (BCVA of 75 letters) were analyzed. Results. Seventy-seven eyes of DME patients were subjected to the final analysis. Bevacizumab treatment reduced CMT from 425.06 μm (±77.15) to 350.25 μm (±82.04) and improved BCVA by about 8.61 letters (from 64.73 to 73.34) in the patients. The mean number of MAs in SCP decreased from 3.51±2.07 to 2.31±1.15 (p<0.001) and in DCP from 17.12±11.56 to 12.21±6.99 (p<0.001), whereas the area of FAZ increased in SCP from 328.22±131.38 to 399.70±156.98 (p<0.001) and in DCP from 571.13±396.01 to 665.89±412.77 (p=0.001). The final BCVA letter score and CMT were statistically significant in both poor and good responders, as well as in BCVA<75 and BCVA≥75 groups. Conclusion. The fixed-regimen intravitreal bevacizumab therapy was effective in treating DME. Apart from noninvasive visualization of microvascular damage, OCT-A showed limited usefulness in predicting treatment response. Although the study showed that the number of MAs was significantly reduced during treatment, which is an OCT-A predictor of a good response to bevacizumab treatment at a 12-month visit, commonly observed artifacts may reduce the usefulness of OCT-A.